Factors associated with cervical cancer screening among women of reproductive age in Ghana - Sulemana Ansumah Saaka; Mohammed-Gazali Hambali (BMC, 2024)
Abstract Background Cervical cancer remains a leading cause of cancer-related deaths among women in Ghana and other Sub-Sahara African (SSA) countries. Despite the importance of early diagnosis for timely treatment and death prevention, cervical cancer screening among women in developing countries remain very low. Nonetheless, there is a paucity of research examining the factors associated with screening uptake among women of reproductive age in Ghana. Thus, this study fills the scholarly void and contributes to the existing literature by examining the determinants of cervical cancer screening in Ghana. Methods Utilizing data from the 2022 Ghana Demographic and Health Survey (GDHS) (N = 15,014 women), and by employing logistic regression models for a cross-sectional analysis, this study evaluated the factors associated with cervical cancer screening in Ghana. Results Women with tertiary educational attainment (OR = 4.140; 95%CI: 2.960 5.789; p < 0.001), from the richer (OR = 1.968; p < 0.001) and richest households (OR = 2.492; p < 0.001), the married/living with partner (OR = 1.773; 95%CI:1.372 2.290; p < 0.001), the widowed/divorced/separated (OR = 1.888; 95%CI:1.320 2.701; p < 0.001), owners of valid health insurance card (OR = 1.356; 95%CI:1.086 1.693; p < 0.01), visitation to health facility in the past 12 months (OR = 1.312; 95%CI: 1.082 1.590; p < 0.001), those who watched television at least once in a week (OR = 1.395; 95%CI: 1.055 1.846; p < 0.001), as well as those who listened to radio at least once in a week (OR = 1.509; 95%CI: 1.228 1.853; p < 0.001), were all significantly more associated with cervical cancer screening in the study context. Also, ethnicity, religion, and the region of residence significantly predicted cervical cancer screening in the study context. Conclusion Cervical cancer screening in Ghana can be improved by addressing socioeconomic and geographical disparities in the country's healthcare system. To ensure early detection, timely treatment or care and prevention of cervical cancer-related deaths in the country, there must be coordinated efforts by the government of Ghana to improve healthcare access and surveillance systems for cervical cancer cases, particularly, in geographically disadvantage areas.